Sistem Pendukung Keputusan Untuk Pemilihan Peserta Didik Berprestasi Di SD N 1 Tegineneng Menggunkan Metode VIKOR - Dinilhaq, Ridho Afdol; Sulistianing Budi, Wahyu (YHMM PUBLISHING, 2025)
The selection of outstanding students at the elementary school level is an important effort to recognize academic and non-academic achievements. However, manual assessment processes often lead to subjectivity and inefficiency. This study aims to develop a Decision Support System (DSS) to assist in selecting outstanding students at SD N 1 Tegineneng using the VIKOR (VlseKriterijumska Optimizacija I Kompromisno Resenje) method. VIKOR is chosen because it provides a compromise solution among conflicting criteria. The criteria used in this system include academic performance, participation in extracurricular activities, discipline, and student attitudes and behavior. Data were collected through observations and interviews with school staff. The test results indicate that the system can provide accurate and objective recommendations based on the mathematical calculations of the VIKOR method. This DSS helps ensure that the selection process is more transparent, efficient, and on target.